1999
DOI: 10.1161/01.atv.19.4.918
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Restriction of Saturated Fat and Cholesterol Decreases HDL ApoA-I Secretion

Abstract: We examined the mechanisms responsible for the decrease in HDL cholesterol (HDL-C) levels after the consumption of a diet low in total fat, saturated fat, and cholesterol. Twenty-one subjects with a mean age of 58+/-12 years were placed on a baseline isocaloric diet (15% protein, 49% carbohydrate, 36% fat, and 150 mg/1000 kcals of cholesterol) and then switched to an NCEP Step 2 diet (15% protein, 60% carbohydrate, 25% fat, and 45 mg/1000 kcals of cholesterol). After 6 or 24 weeks on each diet, subjects receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Concerning the higher HDL cholesterol content in HFD fed animals, despite the fact that dietary saturated fat intake has been associated with increased plasma cholesterol (particularly LDL), paradoxically, saturated fat intake has also been related with elevated HDLc plasma levels 33 . In this regard, it has been observed that low saturated fat and cholesterol intake reduced apolipoprotein A1 secretion 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the higher HDL cholesterol content in HFD fed animals, despite the fact that dietary saturated fat intake has been associated with increased plasma cholesterol (particularly LDL), paradoxically, saturated fat intake has also been related with elevated HDLc plasma levels 33 . In this regard, it has been observed that low saturated fat and cholesterol intake reduced apolipoprotein A1 secretion 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that women may adapt HDL metabolism to shifts in dietary fat and carbohydrate more readily than men (eg, see Reference 40). The HDL rise and fall may represent a protective adaptation to fat feeding that is stronger in women than in men over the long term (as suggested by Vélez-Carrasco et al 48 ). Finally, Brinton et al 49 have speculated that the low fat diet-induced reduction in HDL-C is benign because it is associated with a reduction in apoA-I entry, whereas individuals with primary reductions in HDL-C have enhanced apoA-I removal.…”
Section: Walden Et Al Hdl Andmentioning
confidence: 90%
“…None of the measures of fat intake was associated with HDL-cholesterol (Thorogood et al, 1990). There is good evidence that the replacement of fats by carbohydrates is associated with a decrease of HDLcholesterol (Vélez-Carrasco et al, 1999). The effect is Giessen Wholesome Nutrition Study I Hoffmann et al strongest for the replacement of saturated fatty acids by carbohydrates but also seen for the replacement of monoand polyunsaturated fatty acids (Katan, 1998).…”
Section: Discussionmentioning
confidence: 99%